2014
DOI: 10.2135/cropsci2014.02.0147
|View full text |Cite
|
Sign up to set email alerts
|

Vigor and Persistence of Birdsfoot Trefoil Populations Selected with or without an Orchardgrass Companion Evaluated in Grass Sod

Abstract: RESEARCHI n the United States approximately 37% of nonfederal land in the lower 48 states is either rangeland, pasture, or in the Conservation Reserve Program ( Barnes and Nelson, 2003), although more recent changes in commodity prices likely have caused this number to decline (Wright and Wimberly, 2013). Forage legumes are very often a part of these grasslands and pastures. Forage legume breeders therefore often consider the merits of incorporating grass competition in their variety development programs. Bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Previously, it has been shown that legumes persist less in mixtures because of exploitation by grasses for light and fixed N as earlier mentioned [10]. This scenario is evident from changes in morphological traits [28] as well as resource allocation [29]. Both species traits and management practices influencing forage monocrop persistence have been described in detail by Bouselinck et al [26].…”
Section: The Challenge Of Legume Persistence In Mixed Standsmentioning
confidence: 89%
“…Previously, it has been shown that legumes persist less in mixtures because of exploitation by grasses for light and fixed N as earlier mentioned [10]. This scenario is evident from changes in morphological traits [28] as well as resource allocation [29]. Both species traits and management practices influencing forage monocrop persistence have been described in detail by Bouselinck et al [26].…”
Section: The Challenge Of Legume Persistence In Mixed Standsmentioning
confidence: 89%
“…When measuring crude protein concentration, there was no genetic correlation between the two systems (r= -0.13, not significant). Similarly, Riday & Brummer (2014) demonstrated that selecting birdsfoot trefoil (Lotus corniculatus) with a cocksfoot companion leads to more persistent birdsfoot trefoil varieties for use in grass mixtures than birdsfoot trefoil bred without a grass companion.…”
Section: Phenotypingmentioning
confidence: 99%
“…Forages are frequently grown in grass-legume mixtures ( Riday and Brummer, 2014 ). In alfalfa ( Medicago sativa ), the most widely grown forage crop, planting practices vary by region, with mixtures more common in the northeast and upper Midwestern United States ( Undersander et al, 2011 ).…”
Section: Forage Mixturesmentioning
confidence: 99%
“…In alfalfa ( Medicago sativa ), the most widely grown forage crop, planting practices vary by region, with mixtures more common in the northeast and upper Midwestern United States ( Undersander et al, 2011 ). White clover ( Trifolium repens ) is grown almost exclusively in mixed stands ( Riday and Brummer, 2014 ). In general, legumes are weaker competitors compared to grasses, with the exception of alfalfa which often dominates mixtures when included as the legume component ( Haynes, 1980 ; Zannone et al, 1986 ; Jones et al, 1989 ; Annicchiarico and Proietti, 2010 ; Brophy et al, 2017 ; Maamouri et al, 2017 ).…”
Section: Forage Mixturesmentioning
confidence: 99%
See 1 more Smart Citation